Causes and side effects of changing water quality in Khassa-Chai river in Kirkuk, Iraq - Qasim, Abdulamir H. (Scientific Review Engineering and Environmental Sciences (SREES), 2021)
Water quality of seasonal water rivers is on a quick decline due to various human activities arising as a result of urbanization and population growth. This study assessed the water quality of the Khassa-Chai river in Kirkuk during two seasons: winter and summer (wet and dry). Thirty-seven water samples were collected from eight monitoring observation points along the Khassa-Chai river during October 2019 and March 2020. Water samples were analyzed for various parameters such as temperature, pH, electrical conductivity (EC), turbidity, total suspended solids (TSS), total dissolved solids (TDS), color, and dissolved oxygen (DO). These physicochemical parameters were analyzed using standards methods demonstrated by the American Public Health Association (APHA). To determine the significant difference, all the results obtained were statistically analyzed. In most results, higher concentrations are out of the indicated permissible limits of the World Health Organization (WHO). It can be concluded that the most domestic wastewater effluents are discharged into the river, such as sewage coming from nearby houses and restaurants in addition to the solid waste produced from close commercial stores. To reduce the negative impact on water and human health, pollution sources need to be properly managed. The paper calls for further research to figure out the ability of the Khassa-Chai river to make the use of city water in improving the environment.